Zur Effizienz zentralitätsplanerischer Maßnahmen. Ergebnisse von Folgeuntersuchungen in der Marburger Innenstadt - Buchhofer, E.; Jülich, V.; Jüngst, P. (ERDKUNDE, 1980)
An evaluation of the interviews and counts of passers-by carried out in the inner city of Marburg in 1972, 1974 and 1976 (an additional count was held in 1978) supplied the following main results: - the establishment of a pedestrian zone in the historical part of the inner city (= Oberstadt/upper city) early in 1974 has considerably increased the attraction of this quarter, particularly for people coming from beyond a circle of 25 km. around Marburg. By an increasing specialisation the retailers in this area were generally able to meet the growing competition of department stores. - the rapid trebling of the shopping area in another part of the inner city (= department store area) in 1975 has led to an enormous concentration of purchasing power, partic ularly of the people from the rural surroundings of Marburg. The effect of this investment, trying to increase the centrality of Marburg, was far greater in the area immediately around the city than beyond. - the centrality effects of the two measures apparently do not conflict with each other, because they appeal to different kinds of visitors with different activities. The combination of both measures may be considered as a good example of successful and efficient centrality planning.